(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines linguodidactic challenges in foreign language teaching within the continuing education sstem. It explores effective methodologies, pedagogical principles, and the integration of digital tools to enhance language acquisition. Emphasis is placed on lifelong learning, adaptation to technological advancements, and the development of communicative competence. The article also discusses the role of personalized learning strategies and the necessity of aligning curricula with learners’ cognitive and psychological characteristics. Recommendations for improving teaching practices are provided.